Avaliação do desempenho da tilápia do nilo (Oreochromis niloticus) criadas no sistema de bioflocos - Barbosa, Kleber do Nascimento (2018)
The objective of this work was to analyze the viability of the production of Nile Tilapia (Oreochromis niloticus) in a biofloc production system. The work was carried out on the Anzol Pescado Restricted property, located in the city of Remígio - PB, from December 13 to February 28, 2018. In the experiment for that study, a 14.3m diameter geomembrane tank was set up and 1 of depth, making a total of 180 m³, with a system of aeration of porous hoses of the company Aquadrop specifically the hose M25, pipes pvc, a blower of air of 1,5 HP. In order to analyze the water parameters and the growth of the animals in the property, a multiparameter, IMHOFF cone and a precision scale were used. We used commercial storage density of 33.5 / m3 fish, making a total of 6,000 fish in the tank. The water quality was analyzed throughout the experiment, and the following physical and chemical parameters were measured: temperature, dissolved oxygen, pH, alkalinity, total solids, total hardness, ammonia and nitrite. The fish were fed commercial Aquavita rations with 3 percent crude protein; 45% that was used in the initial phase precisely in the first 15 days of cultivation, shortly after that of 36% that was supplied for 11 days and then the 32% that was offered during the rest of the experiment. This ration was offered 4 times a day at the times of 7, 10, 13 and 16 hours. The amount of feed given to the fish daily was according to the weight average obtained by biometrics. The activation of bioflocos constituted through the use of molasses as carbon source and probiotic. The amount of molasses applied in the system was done according to the results of the analyzes of total ammonia (NH4) and nitrite (NO2), thus employing a C: N ratio of 20: 1. Biometrics were weighed 5 batches of 10 animals totaling 50 animals, where after weighing an average was made to measure the weight per animal unit. This weighing was done weekly in the interval of 7 days from one weighing to another. The performance of the Tilapia cultivated in the biofloc system was evaluated according to the following parameters: Final weight, Gain in weight and apparent feed conversion. The experiment was evaluated through Principal Component Analysis (PCA) through the SAS software to compare and analyze the data found. The results regarding the performance of Tilapia cultivated in the biofloc system were positive, with a final weight of 143 g and a feed conversion of 0.73 in 77 days. By monitoring the physical-chemical parameters of water, external environment, biometrics and zootechnical indexes, we can say that the production of Nile Tilapia (Oreochromis niloticus) in a bioflocosystem is feasible.